China asked Russia to delay Ukraine war until after Olympics, US officials say - Wong, Edward; Barnes, Julian E. (Periódicos Brasil. Pesquisa Científica, 2022)
SUMMARY This document is a shared copy of a journalistic article from the New York Times, written by journalists Edward Wong and Julian E. Barnes. This sharing does not have the prior consent or authorization of the New York Times or its journalistic authors and follows only the principles of free information and freedom of expression. This sharing will not be complete and if the reader wants to have access to the metrics in full, just click on the link to the original material below, in References. INTRODUCTION TO THE SUBJECT WASHINGTON — A Western intelligence report said senior Chinese officials told senior Russian officials in early February not to invade Ukraine before the end of the Winter Olympics in Beijing, according to senior Biden administration officials and a European official. The report indicates that senior Chinese officials had some level of direct knowledge about Russia’s war plans or intentions before the invasion started last week. President Vladimir V. Putin of Russia met with President Xi Jinping of China in Beijing on Feb. 4 before the opening ceremony of the Olympics. Moscow and Beijing issued a 5,000-word statement at the time declaring that their partnership had “no limits,” denouncing NATO enlargement and asserting that they would establish a new global order with true “democracy.” The intelligence on the exchange between the Chinese and Russian officials was classified. It was collected by a Western intelligence service and considered credible by officials. Senior officials in the United States and allied governments passed it around as they discussed when Mr. Putin might attack Ukraine. However, different intelligence services had varying interpretations, and it is not clear how widely the information was shared. One official familiar with the intelligence said the material did not necessarily indicate the conversations about an invasion took place between Mr. Xi and Mr. Putin. Other officials briefed on the intelligence declined to give further details. The officials spoke about the report on the condition of anonymity because of the sensitivity of the intelligence. Given the close nature of the relationship between Mr. Xi and Mr. Putin, senior Chinese officials are likely to have briefed Mr. Xi on any important exchanges between officials of their nations in the period around the leadership summit, analysts say. When asked by email on Wednesday whether Chinese officials had urged Russian officials to delay an invasion of Ukraine until after the Olympics, Liu Pengyu, the Chinese Embassy spokesman in Washington, said, “These claims are speculation without any basis, and are intended to blame-shift and smear China.” To continue reading the article, please access the New York Times page at https://www.nytimes.com/2022/03/02/us/politics/russia-ukraine-china.html